VOCATIONAL SCHOOL STUDENTS' PERCEPTIONS OF GOOGLE CLASSROOM IN FULL ONLINE LEARNING AT THE BEGINNING OF THE COVID-19 PANDEMIC - Dantes, Gede Rasben; Rinawati, Ni Komang Ayu; Suwastini, Ni Komang Arie; Artini, Ni Nyoman (Universitas Pendidikan Ganesha, 2022)
The global Covid-19 pandemic affects all aspects of life, including students learning process. Teachers and students were instructed to